Protein and Microbial Biomarkers in Sputum Discern Acute and Latent Tuberculosis in Investigation of Pastoral Ethiopian Cohort - HaileMariam, Milkessa; Yu, Yanbao; Singh, Harinder; Teklu, Takele; Wondale, Biniam; Worku, Adane; Zewude, Aboma; Mounaud, Stephanie; Tsitrin, Tamara; Legesse, Mengistu; Gobena, Ameni; Pieper, Rembert (Frontiers in Cellular and Infection Microbiology, 2021)
Differential diagnosis of tuberculosis (TB) and latent TB infection (LTBI) remains a public health priority in high TB burden countries. Pulmonary TB is diagnosed by sputum smear microscopy, chest X-rays, and PCR tests for distinct Mycobacterium tuberculosis (Mtb) genes. Clinical tests to diagnose LTBI rely on immune cell stimulation in blood plasma with TB-specific antigens followed by measurements of interferon-γ concentrations. The latter is an important cytokine for cellular immune responses against Mtb in infected lung tissues. Sputum smear microscopy and chest X-rays are not sufficiently sensitive while both PCR and interferon-γ release assays are expensive. Alternative biomarkers for the development of diagnostic tests to discern TB disease states are desirable. This study’s objective was to discover sputum diagnostic biomarker candidates from the analysis of samples from 161 human subjects including TB patients, individuals with LTBI, negative community controls (NCC) from the province South Omo, a pastoral region in Ethiopia. We analyzed 16S rRNA gene-based bacterial taxonomies and proteomic profiles. The sputum microbiota did not reveal statistically significant differences in α-diversity comparing the cohorts. The genus Mycobacterium, representing Mtb, was only identified for the TB group which also featured reduced abundance of the genus Rothia in comparison with the LTBI and NCC groups. Rothia is a respiratory tract commensal and may be sensitive to the inflammatory milieu generated by infection with Mtb. Proteomic data supported innate immune responses against the pathogen in subjects with pulmonary TB. Ferritin, an iron storage protein released by damaged host cells, was markedly increased in abundance in TB sputum compared to the LTBI and NCC groups, along with the α-1-acid glycoproteins ORM1 and ORM2. These proteins are acute phase reactants and inhibit excessive neutrophil activation. Proteomic data highlight the effector roles of neutrophils in the anti-Mtb response which was not observed for LTBI cases. Less abundant in the sputum of the LTBI group, compared to the NCC group, were two immunomodulatory proteins, mitochondrial TSPO and the extracellular ribonuclease T2. If validated, these proteins are of interest as new biomarkers for diagnosis of LTBI.